2013
DOI: 10.1039/c3ra22789h
|View full text |Cite
|
Sign up to set email alerts
|

The design and synthesis of novel “turn-on” fluorescent probes to visualize monoamine oxidase-B in living cells

Abstract: We report the design and synthesis of a new class of fluorogenic probes based on a monoamine oxidase-B (MAO-B)-catalyzed a-carbon oxidation-hydrolysis mechanism. The cell-permeable probes exhibited good selectivity and sensitivity towards MAO-B, and a turn-on response in fluorescence intensity in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…A vanillic acid amide had the best antifungal activity result, so five derived esters (compounds 23 – 27 ) and five derived ethers (compounds 28 – 32 ) of this vanillic acid amide ( 15 ) were prepared using reaction methods for replacing the vanillic ring OH group with an ether or ester chain. All ester and ether derivatives are reported for the first time in the literature and their spectroscopic data were in agreement with the literature data of structurally similar compounds [18,19,20,21,22,23,24,25,26].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A vanillic acid amide had the best antifungal activity result, so five derived esters (compounds 23 – 27 ) and five derived ethers (compounds 28 – 32 ) of this vanillic acid amide ( 15 ) were prepared using reaction methods for replacing the vanillic ring OH group with an ether or ester chain. All ester and ether derivatives are reported for the first time in the literature and their spectroscopic data were in agreement with the literature data of structurally similar compounds [18,19,20,21,22,23,24,25,26].…”
Section: Resultssupporting
confidence: 88%
“…The extraction solution was washed with distilled water (3 × 10 mL), and then with 10% NaOH (10 mL). The solution was treated with Na 2 SO 4 , filtered, and concentrated by rotary evaporation [24]. The product was purified by silica gel column chromatography using EtOAc:Hex (65:35) as the mobile phase system to afford a colorless oil; yield: 75% (106 mg), IR ν max (cm −1 ): 3350 (OH) 3016 (CH sp 2 ), 1645 (C=O), 1600 and 1489 (aromatic C=C), 1014 (stretching C-Cl).…”
Section: Methodsmentioning
confidence: 99%
“…10 Fluorescent probe offers a unique approach for visualizing morphological details of tissues with subcellular resolution and has become a powerful tool for manipulating and investigating living cells and even animals. [11][12][13][14] There are different kinds of uorescent probes with various skeleton structure, including rhodamine, 15 BODIPY, 16 uorescein, 17 tricarbocyanine, 18 benzo[a]phenoxazine, 19 coumarin 20 etc. From these uorophores, some special probes with pH sensitivity can be designed and synthesized by changing functional groups to these skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…In a further study, they reported fluorescein derivatives 13 and their use for bioimaging. 46 Probe 13a, however, gave only about three times higher fluorescence enhancement to MAO-B over MAO-A (K m (13a/MAO-A) = 257.9 μM, K m (13a/MAO-B) = 47.1 μM).…”
Section: −1mentioning
confidence: 99%